CRISPR/Cas9-facilitated engineering with growth-coupled and sensor-guided in vivo screening of enzyme variants for a more efficient chorismate pathway in E. coli - Chen, Minliang; Chen, Lin; Zeng, An-Ping (Metabolic engineering communications, 2019)
Protein engineering plays an increasingly important role in developing new and optimizing existing metabolic pathways for biosynthesis. Conventional screening approach of libraries of gene and enzyme variants is often done using a host strain under conditions not relevant to the cultivation or intracellular conditions of the later production strain. This does not necessarily result in the identification of the best enzyme variant for in vivo use in the production strain. In this work, we propose a method which integrates CRISPR/Cas9-facilitated engineering of the target gene(s) with growth-coupled and sensor-guided in vivo screening (CGSS) for protein engineering and pathway optimization. The efficiency of the method is demonstrated for engineering 3-deoxy-D-arabino-heptulosonate-7-phosphate (DAHP) synthase AroG, a key enzyme in the chorismate pathway for the synthesis of aromatic amino acids (AAAs), to obtain variants of AroG (AroGfbr) with increased resistance to feedback inhibition of Phe. Starting from a tryptophan (Trp)-producing E. coli strain (harboring a reported Phe-resistant AroG variant AroGS180F), the removal of all the endogenous DAHP synthases makes the growth of this strain dependent on the activity of an introduced AroG variant. The different catalytic efficiencies of AroG variants lead to different intracellular concentration of Trp which is sensed by a Trp biosensor (TnaC-eGFP). Using the growth rate and the signal strength of the biosensor as criteria, we successfully identified several novel Phe-resistant AroG variants (including the best one AroGD6G−D7A) which exhibited higher specific enzyme activity than that of the reference variant AroGS180F at the presence of 40 mM Phe. The replacement of AroGS180F with the newly identified AroGD6G−D7A in the Trp-producing strain significantly improved the Trp production by 38.5% (24.03 ± 1.02 g/L at 36 h) in a simple fed-batch fermentation. •A novel approach for phenotype-focused and product-targeted in vivo screening of enzyme variants.•AroG variant with high resistance to feedback inhibition of phenylalanine.•Tryptophan production in E. coli improved by 38.5% with the new variant AroGD6G−D7A.